RETRACTED: Pengembangan Model Simboling Kelompok Expressive Writing berlandaskan Falsafah Dandang Tingang untuk Meningkatkan Perilaku Respect: RETRACTED: Development of the Simboling Model of Expressive Writing Groups based on the Dandang Tingang Philosophy to Improve Respect Behavior - Karyanti, Karyanti; Setiawan, Muhammad Andi (Anterior Jurnal, 2019)
This article has been retracted as a result of multiple publications from the article by the relevant author. Similar articles can be found at the URL https://journal.stkip-andi-matappa.ac.id/index.php/jurkam/article/view/204 or https://dx.doi.org/10.31100/jurkam.v3i1.204